Korelasi manajemen penghargaan dan sanksi dengan tingkat kedisiplinan pegawai - Fi'liyah, Ma'rifatul (Maliki Interdisciplinary Journal, 2024)
This article aims to examine the influence of reward and punishment management on the level of discipline of Malang Regency DPRD secretariat employees. Discipline is a critical factor in maintaining the efficiency and effectiveness of regional legislative institutions. This research is classified as qualitative research which was conducted using survey methods and structured interviews with secretariat employees of the Regional Representative Council of Malang Regency, East Java, Indonesia. The research results show that the correlation between reward management implemented in the Malang Regency DPRD has a positive influence on the level of discipline of secretarial employees. Providing rewards that are fair and appropriate to employees' work contributions encourages them to maintain a high level of discipline. The results show that reward and punishment management regarding the level of discipline in the Malang Regency DPRD secretariat is relatively dependent on the good relationship that exists with superiors.